2009
DOI: 10.1021/ja9067645
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction on Well-Defined Core−Shell Nanocatalysts: Particle Size, Facet, and Pt Shell Thickness Effects

Abstract: We examined the effects of the thickness of the Pt shell, lattice mismatch, and particle size on specific and mass activities from the changes in effective surface area and activity for oxygen reduction induced by stepwise Pt-monolayer depositions on Pd and Pd(3)Co nanoparticles. The core-shell structure was characterized at the atomic level using Z-contrast scanning transmission electron microscopy coupled with element-sensitive electron energy loss spectroscopy. The enhancements in specific activity are larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
665
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 716 publications
(694 citation statements)
references
References 31 publications
26
665
2
1
Order By: Relevance
“…We ascribe the latter effect to Ru-induced lattice contraction and the smooth morphology obtained both by the annealed Ru cores and by coating Pt under near-equilibrium conditions to enhance the formation of energetically favourable structure. Previous studies have shown that the less reactive a surface is, the more corrosion resistant it is 7,8,11 ; low coordination sites (clusters, defects, vertices and edges) are prone to dissolution, and thus need to be minimized 8,11 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We ascribe the latter effect to Ru-induced lattice contraction and the smooth morphology obtained both by the annealed Ru cores and by coating Pt under near-equilibrium conditions to enhance the formation of energetically favourable structure. Previous studies have shown that the less reactive a surface is, the more corrosion resistant it is 7,8,11 ; low coordination sites (clusters, defects, vertices and edges) are prone to dissolution, and thus need to be minimized 8,11 .…”
Section: Resultsmentioning
confidence: 99%
“…At the cathode, Pt monolayer (ML) catalysts with Pd or Pd 9 Au alloy cores exhibited enhanced activity and durability for the oxygen reduction reaction compared with Pt NPs 3 . Furthermore, both experimental and theoretical studies verified that lattice contraction [4][5][6][7] , high-coordination (111) facets [8][9][10] and smooth surface morphology 11 are beneficial structural factors in enhancing oxygen reduction reaction activity and the catalysts' durability.…”
mentioning
confidence: 90%
“…Peng et al [208] also found improved stability for ORR with a Pt-on-Pd core-shell nanostructure. It was calculated that the optimal coverage of Pt on Pd (111) surface was on the order of two monolayers [271]. Yang et al [209] prepared a core-shell structure with a PdFe core and a PdPt shell, which showed four times ORR activity compared with a commercial Pt/C catalyst.…”
Section: Core-shell Structuresmentioning
confidence: 99%
“…The lattice contraction will weaken the surface oxygen binding energy and reduce the coverage of intermediate oxygen species, giving rise to the enhanced ORR activity relative to the Pt nanoparticles of Pt/C and the Pt shell on the surface of Pd@Pt NDs [42,43]. Another reason can be ascribed to the relatively smooth surface feature of the NCs compared to that of the Pt/C and Pd@Pt NDs [9,44].…”
Section: Electrocatalytic Performancesmentioning
confidence: 99%